Forest Management - Chaturvedi, M. D. (Indian Forester, 1950)
Forest management in India continues to be inspired by the ideal of sustained yield enunciated by Dr. Brandis in 1856. Following the prescribed pattern to a fault, Indian working plans have shown resilient adaptability to changes brought about by industrial advancement actuated by two major wars. Management practices in legally constituted State forests have reacted to recent trends in management and development of silvicultural technique. Increased demand for structural timber during the post-war period; new demands for lesser known timbers for manufacture of bobbins, matches, plywood, paper and rayon; and the inordinate demand for firewood find reflection in recent working-plans. No less important is the bearing which mechanized transport, disposal, conversion and treatment of forest produce has had on forest management. 2. The progressive realization of the role of forests in the economy of a predominantly agricultural country like India has attracted the attention of Provincial Governments to the need of the conservation of private forests and the creation of firewood and fodder reserves on wastelands and State lands such as canal banks, railway lands, camping grounds, etc. Management of such forests is particularly designed to provide firewood to divert farm-yard manure from village hearths to village fields.